Strategies to enhance resilience to cope with workplace adversities post-COVID-19 among ICU nurses - Nombulelo E. Zenani; Gopolang Gause; Leepile Sehularo (AOSIS, 2022)
Background: It is critical for intensive care unit (ICU) nurses to develop resilient coping strategies to cope with workplace adversities. The coping strategies will mitigate the development of maladaptive psychological disorders prone to working in a stressful environment. Objectives: The aim of this study is to analyse previous literature conducted on strategies that enhance resilience in ICU nurses to cope with workplace adversities beyond the coronavirus disease 2019 (COVID-19) pandemic. The study was conducted by examining all available global literature in the context of the aim of the study. Method: An integrative literature review was chosen for the study. Purposive sampling method was used to select the relevant databases to answer the review question, namely Google Scholar, EBSCOhost, Medline and Nursing/Academic Edition. The search terms used were 'strategies', 'resilience', 'intensive care unit nurses', 'coping', 'workplace adversities', 'beyond COVID-19' and post 'COVID-19'. Results: Three themes emerged from the study, namely promoting personal attributes, effective relational support and active psychological support. Conclusion: Enhancing resilience among ICU nurses requires both intentional individualised care from the ICU nurses and a systematic approach by nursing management that will meet the psychological needs of ICU nurses when working in a stressful ICU environment. Contribution: The findings of the review have highlighted specific strategies of improving resilience in ICU nurses, which can ultimately create a safe working environment in the ICU.